Application of Point of Sales Technology in Mobile-Based Bayu Kusuma Stores with Rapid Application Development Method - Thahira, Salsabilla; Suendri, Suendri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Bayu Kusuma Wholesale Store currently has problems recording transactions. Recording transactions at this grocery store uses a conventional method. Where employees record transactions on the books. This is very detrimental because the number of transactions with available stock is often manipulated. In its completion, a Point of sales technology is needed. transactions made by Bayu Kusuma Wholesale Store via WhatsApp are less effective in providing an online shopping experience. This is because the product catalog and available inventory cannot be displayed directly, making purchasing difficult for customers. In solving this problem, Android-based Point Of Sales technology is needed to record transactions and stock from stores. The Rapid Application Development method is used to solve store problems so that the system is built according to the needs of the store and completes the review of the store that occurs. The results showed that POS used to help process transactions can increase productivity and efficiency in job responsibilities. This can be seen where customers do not need to come to the store to get the product, but order first through the application then bring the item to the store and make payment in cash.